2001
DOI: 10.1159/000045883
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Renal Amyloidosis: A Clinicopathological Study Using Cluster Analysis

Abstract: Progression of renal amyloidosis is associated with severe proteinuria or nephrotic syndrome, and various mechanisms have been postulated to explain these complications. We studied the acceleration of proteinuria and reduced renal function by cluster analysis using clinical parameters, renal histological findings, type of renal amyloidosis and follow-up data. We divided 97 cases into three groups of renal amyloidosis. Accelerated progression correlated with serum creatinine (s-Cr) levels at renal biopsy and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 11 publications
1
14
1
Order By: Relevance
“…Gertz et al [11] analyzed 64 patients with AA amyloidosis and demonstrated that renal dysfunction (serum creatinine value of > 2 mg/dl) at presentation is strongly associated with shorter survival. Other studies confirmed that serum creatinine concentration is an important predictive factor for the survival of AA amyloidosis patients, as well [16,18]. In the present study, a finding deserves special mention: although low serum albumin was the strongest predictor of death, proteinuria did not show this significance.…”
Section: Discussionsupporting
confidence: 72%
“…Gertz et al [11] analyzed 64 patients with AA amyloidosis and demonstrated that renal dysfunction (serum creatinine value of > 2 mg/dl) at presentation is strongly associated with shorter survival. Other studies confirmed that serum creatinine concentration is an important predictive factor for the survival of AA amyloidosis patients, as well [16,18]. In the present study, a finding deserves special mention: although low serum albumin was the strongest predictor of death, proteinuria did not show this significance.…”
Section: Discussionsupporting
confidence: 72%
“…The farming accident may have promoted this condition. AA amyloidosis induces more extensive amyloid deposits on the tubular basement membrane, interstitial tissue, and arteriolar walls of the kidneys and rapidly worsens the prognosis of patients compared to AL amyloidosis [13]. In our case, amyloid deposition on the tubular basement membrane and arteriolar walls of the kidneys was more intense than that previously reported [14].…”
Section: Discussioncontrasting
confidence: 49%
“…Only a few studies have investigated the individual survival rate (4,38). Renal amyloidosis is associated with increased mortality in hemodialysis patients (36,39) and in patients with rheumatoid arthritis (40).…”
Section: Some Reports Have Claimed That Renal Failure or Renal Dysfunmentioning
confidence: 99%
“…Several outcome studies have discussed the onset and progressive mechanisms of renal amyloidosis; however, detailed analyses of a large number of cases have not been undertaken (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%